STRATEGI KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DALAM MENDORONG TRANSFORMASI DIGITAL SEKOLAH DI SMK NEGERI CAMPAKA - Darlina; Ajat Rukajat; Achmad Taufik Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This journal examines the digital leadership strategies employed by school principals in fostering digital transformation at SMK Negeri Campaka. In the era of rapid technological advancement, educational institutions face the imperative to integrate digital technologies into their operational and pedagogical processes. This study investigates how principals leverage digital competencies, vision, and strategic planning to guide their organizations through digital transformation. The research employs a qualitative approach to explore the key dimensions of digital leadership, including digital literacy, change management, technology adoption, and stakeholder engagement. Findings reveal that effective digital leadership requires not only technical knowledge but also the ability to inspire organizational culture change, build collaborative networks, and align digital initiatives with institutional goals. The study highlights the critical role of principals in establishing an enabling environment for digital innovation, supporting teacher professional development, and ensuring equitable access to digital resources. The implications of this research contribute to understanding how educational leaders can effectively navigate digital transformation to enhance teaching and learning outcomes.